A high-performance self-powered photodetector based on a concentric annular α-FAPbI3/MAPbI3 single crystal lateral heterojunction with broadband detectivity. Issue 33 (3rd August 2022) - Zhang, Hu; Chen, Zhiliang; Li, Yanhui; Yao, Jianfeng; Liu, Duanwangde; Zeng, Wei; Gui, Pengbin; Huang, Zhixiang
Abstract : α-FAPbI3 /MAPbI3 single crystal concentric annular lateral heterojunction is successfully fabricated by rheotaxy. The device exhibits high performance and wide spectrum response as well as self-driven ability, showing its broad application prospect. Abstract : Heterojunctions were widely studied as semiconductor structures for photoelectronic devices such as solar cells and photodetectors, due to their ability for dark current reduction and self-powered operation. In this work, an α-FAPbI3 /MAPbI3 single crystal concentric annular lateral heterojunction was successfully fabricated by liquid phase epitaxy under ambient conditions. Compared to a vertical heterojunction structure, a lateral structure can reduce the incident light loss and interfacial accumulation of defects. In addition, the selection of the same halogen sites can resolve the issue of phase separation stemming from different halogen ions in the perovskite materials. By fabricating an α-FAPbI3 /MAPbI3 single crystal concentric annular lateral heterojunction, a wide spectrum response from ultraviolet to near-infrared is attained. Furthermore, depending on the reduction of the potential barrier due to the pyro-phototronic effect generated by the MAPbI3 single crystals and the presence of the built-in electric field, the α-FAPbI3 /MAPbI3 single crystal lateral heterojunction-based photodetector exhibits a high responsivity of 27.50 mA W −1, a specific detectivity of 7.71 × 10 11 Jones, a fast response speed of 62.7 μs and self-powering ability. These results suggest that lateral perovskite single crystal heterojunctions with the same halogen are promising configurations for photodetectors and other optoelectronic devices and systems.